PERUBAHAN SIFAT FISIK BIJI KANGKUNG SELAMA PENYIMPANAN (Physical Properties Condition of Ipomea reptans Seeds During Storage) - M. H. Septian; Iman Hernaman; Rachmat Wiradimadja (Jurnal Ilmu dan Teknologi Peternakan, 2018)
Ipomea reptans seeds have been widely used as alternative feed and usually before use for livestock was stored in the storage. This experiment was aimed to study of physical properties condition of Ipomea reptans seeds during storage. The experiment was arranged in a completly randomized design. The collected data was analyzed using Duncan’s test. Twenty-five sacks was contained Ipomea reptans seeds as much as 20 kg into 5 treatment with storage duration of 0, 1, 2, 3, and 4 weeks, then each measured water content and physical properties. The result showed that the long storage had significantly (P <0.05) increased the water content, but decreased (P <0.05) specific gravity, bulk density, and compacted bulk density. The pattern of relationship between duration of storage and water content of Ipomea reptans seeds formed regression equation y = 1.5652X + 8.4536, with value R2 = 0,9193. The Conclusion, long storage can cause changes physical properties of Ipomea reptans seeds.